XRMA and ToF-SIMS Analysis of Normal and Hypomineralized Enamel. (12th February 2015) - Melin, Lisa; Lundgren, Jesper; Malmberg, Per; Norén, Jörgen G.; Taube, Fabian; Cornell, David H.
Abstract: Molar incisor hypomineralization (MIH) is a developmental disturbance of the enamel. This study presents analyses of hypomineralized and normal enamel in first molar teeth diagnosed with MIH, utilizing time-of-flight secondary ion mass spectrometry area analyses and X-ray microanalysis of area and spot profiles in uncoated samples between gold lines which provide electrical conductivity. Statistical analysis of mean values allows discrimination of normal from MIH enamel, which has higher Mg and lower Na and P. Inductive analysis using complete data sets for profiles from the enamel surface to the enamel–dentin junction found that Mg, Cl and position in the profile provide useful discrimination criteria. Element profiles provide a visual complement to the inductive analysis and several elements also provide insight into the development of both normal and MIH enamel. The higher Mg content and different Cl profiles of hypomineralized enamel compared with normal enamel are probably related to a relatively short period during the development of ameloblasts between birth and the 1st year of life.